The refinement of protective salinity guidelines for South African freshwater resources - Slaughter, Andrew Robert (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2005)
South Africa is an arid country and its growing population is putting freshwater resources under increasing pressure. Natural salinization of freshwater systems is being exacerbated by anthropogenic influences. The National Water Act (No. 36 of 1998) stipulates the need for an ecological Reserve, that quantity and quality of freshwater needed to protect freshwater ecosystems while allowing sustainable use of freshwater resources. Water guidelines do exist in the form of the South African Water Quality Guidelines (DWAF, 1996) and more recently, Jooste and Rossouw (2002) compiled benchmark values for water quality variables marking the boundaries between ecological health classes in the 4-category classification system. Predominantly international toxicity data were used to compile the guidelines and the benchmark values. In addition, there is a paucity of chronic toxicity data nationally and internationally. This thesis showed that it is statistically possible to derive protective chronic endpoints for salinity from acute toxicity data through extrapolation. The Acute to Chronic Ratio (ACR), Two-Step Linear Regression (LRA) and Multi-Factor Probit Analysis (MPA) extrapolation methods were investigated to derive chronic toxicity data from acute toxicity data. The authors of LRA and MPA recommend associating a time independent LCx value in the range of LCâ‚€Â¸â‚€â‚ to LCâ‚ â‚€ with a Predicted No Effect Concentration (PNOEC). In addition to published methods, this thesis studied the possibility of equating a time independent LCâ‚…â‚€ value and subjected to a safety factor of 5 (LRA LCâ‚…â‚€/5), to the PNOEC. Extrapolated chronic toxicity data where the toxicants are NaCl and Naâ‚‚SOâ‚„ were derived for indigenous South African macroinvertebrates. NaCl and Naâ‚‚SOâ‚„ are salts associated with salinisation in South Africa. In addition, a chronic salinity toxicity test protocol for an indigenous South African aquatic macroinvertebrate was designed and chronic toxicity test were performed using NaCl and Naâ‚‚SOâ‚„ as toxicants. The experimental chronic toxicity data produced were used to validate results from the acute to chronic extrapolation methods. Extrapolated chronic toxicity data were inputted into Species Sensitivity Distribution curves, and concentrations that were predicted to protect 95 % of species (PC95) were compared to the sub-lethality benchmarks proposed by Jooste and Rossouw (2002) for NaCl and Naâ‚‚SOâ‚„. This study concluded that the LRA LCâ‚…â‚€/5 extrapolation method is the most protective and accurate and proposed that LRA replace the ACR method in future guideline development for inorganic salts.
Keywords: Water salinization -- South Africa; Salinization -- Control -- South Africa; Salinity -- South Africa; Freshwater ecology -- South Africa; Water resources development -- South Africa; Caridina Caridina -- Effect of pollution